Peran Kinerja Pegawai Penyedia Jasa Lainnya Perorangan Terhadap Kepuasan Warga Pada Ruang Publik Terpadu Ramah Anak Kecamatan Kebon Jeruk Jakarta Barat - Abdul Kohar; Ahmad Fadli; Moh.Tahang; Mutiarani Mutiarani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to determine employee performance in Child-Friendly Integrated Public Spaces, Kebon Jeruk District, West Jakarta, residents' satisfaction in Child-Friendly Integrated Public Spaces, Kebon Jeruk District, West Jakarta. and the role of Employee Performance on Citizen Satisfaction in Child- Friendly Integrated Public Spaces, Kebon Jeruk District, West Jakarta.This research method is a qualitative description through interviews with informants as key informants who explain or describe the effect of employee performance on citizen satisfaction in Child-Friendly Integrated Public Spaces, Kebon Jeruk District, West Jakarta. And through Focus Group Discussion (FGD) which is a group interview that emphasizes interaction on the topics discussed. This study also describes testing the validity of the data, the validity of the data or the credibility of the data, namely in observation, perseverance, discussion and study as well as analysis of the satisfaction of these residents.The results of the study showed that there was a value gap in the views of officials who were interviewed and discussed with community groups who were also interviewed by researchers. So the need for a researcher's perspective and confirms that performance is a substantial factor in creating maximum work. Thus the role of performance on citizen satisfaction in the Child-Friendly Integrated Public Space, Kebon Jeruk District, West Jakarta, is very important. Not only encouraging the creation of new values in understanding citizen satisfaction.